Clinical and preclinical approach in AGA treatment: a review of current and new therapies in the regenerative field - Pozo-Pérez, Lorena; Tornero-Esteban, Pilar; López-Bran, Eduardo (Stem cell research & therapy, 2024)
Androgenetic alopecia (AGA) is the most prevalent type of hair loss. Its morbility is mainly psychological although an increased incidence in melanoma has also been observed in affected subjects. Current drug based therapies and physical treatments are either unsuccessful in the long term or have relevant side effects that limit their application. Therefore, a new therapeutic approach is needed to promote regenerative enhancement alternatives. These treatment options, focused on the cellular niche restoration, could be the solution to the impact of dihydrotestosterone in the hair follicle microenvironment. In this context emerging regenerative therapies such as Platelet-rich plasma or Platelet-rich fibrine as well as hair follicle stem cells and mesenchymal stem cell based therapies and their derivatives (conditioned medium CM or exoxomes) are highlighting in the evolving landscape of hair restoration. Nanotechnology is also leading the way in AGA treatment through the design of bioinks and nanobiomaterials whose structures are being configuring in a huge range of cases by means of 3D bioprinting. Due to the increasing number and the rapid creation of new advanced therapies alternatives in the AGA field, an extended review of the current state of art is needed. In addition this review provides a general insight in current and emerging AGA therapies which is intented to be a guidance for researchers highlighting the cutting edge treatments which are recently gaining ground.